The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1089/neu.2022.0217
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation Monitoring in Traumatic Brain Injury: An Overview of Recent Advances in Personalized Medicine

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 138 publications
0
13
0
Order By: Relevance
“…Compared with the aforementioned uncontrollable influencing factors, we first notice that the amplitude of instant change in CBF reperfusion is controllable to some extent. It is also an important factor affecting CBF reperfusion in patients with abnormal cerebral vascular autoregulation (27)(28)(29). Tamaki et al (30) found that the quick evacuation of the hematoma could decrease the intracranial pressure sharply and, at the same time, trigger a severe aggravation of hemodynamic change, thus worsening the overload injury to the decompensated cerebral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the aforementioned uncontrollable influencing factors, we first notice that the amplitude of instant change in CBF reperfusion is controllable to some extent. It is also an important factor affecting CBF reperfusion in patients with abnormal cerebral vascular autoregulation (27)(28)(29). Tamaki et al (30) found that the quick evacuation of the hematoma could decrease the intracranial pressure sharply and, at the same time, trigger a severe aggravation of hemodynamic change, thus worsening the overload injury to the decompensated cerebral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies evaluating CA capacity in ABI focused on intermittent methods for CA determination including various neuroimaging modalities such as positron emission tomography (PET) and computed tomographic xenon (XE-CT) as well as indirect CBF estimation with transcranial doppler (TCD) in response to alterations in MAP either with vasopressors or non-invasively with techniques such as thigh-cuff deflation and orthostatic hypotension provocation ( 10 , 33 ). More recently, novel methods have been developed for continuous assessment of CA indices based on CBF responses to spontaneous changes in MAP or cerebral perfusion pressure CPP and are outlined in Table 1 ( 44 ).…”
Section: Cerebral Physiologymentioning
confidence: 99%
“…This multifaceted approach has begun to reshape the landscape of neurocritical care by moving away from standardized “one size fits all” treatment strategies to individualized precision medicine; however, questions still exist including how to best integrate and interpret the high dimensionality of signals and whether such an approach will result in improved patient outcomes ( 3 , 9 ). Furthermore, when interpreting monitoring data, it is important to recognize potential limitations of each modality and specific characteristics including whether it provides continuous or intermittent assessment as well as if the device is measuring focal or global cerebral parameters ( 10 , 11 ). Common neuromonitoring tools employed in the neurologic intensive care unit (ICU) are highlighted in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…PRx has been demonstrated to be capable of adequately predicting the lower limit of cerebral autoregulation (LLA), but the upper limit of cerebral autoregulation (ULA) is not easily predictable [22,23]. Other tools also have had difficulties to predict the ULA, and it even might be that there is no strict ULA, and cerebral autoregulation is better in compensating for hypotension than for hypertension [24 ▪▪ ]. In retrospective series, it was found that when PRx is plotted against its corresponding CPP, in 60–70% of patients, this leads to a U-shaped curve, in which the lowest (i.e.…”
Section: Estimating Cerebral Autoregulationmentioning
confidence: 99%
“…As they all measure a different parameter, they are not quite redeemable. Because the benefit of treatment protocols based on these metrics has not been unequivocally demonstrated in large prospective patient trials, their use cannot be recommended for clinical use so far [24 ▪▪ ,30].…”
Section: Estimating Cerebral Autoregulationmentioning
confidence: 99%